Developmental gene networks: a triathlon on the course to T cell identity - Yui, Mary A. (2014)
Cells acquire their ultimate identities by activating combinations of transcription factors that initiate and sustain expression of the appropriate cell-type specific genes. T-cell development depends on the progression of progenitor cells through three major phases associated with distinct transcription factor ensembles that control their recruitment to and proliferation in the thymus, their lineage commitment, and their responsiveness to T-cell receptor (TCR) signals, before the allocation of cells to particular effector programs. All three phases are essential for proper T cell development, as are the mechanisms that determine the boundaries between each phase: cells failing to shut off one set of regulators before the next gene network phase is activated are predisposed to leukemic transformation.